2011
DOI: 10.3354/meps09097
|View full text |Cite
|
Sign up to set email alerts
|

Plankton dynamics in an estuarine plume: a mesocosm 13C and 15N tracer study

Abstract: Flows of carbon and nitrogen in a natural phytoplankton assemblage from the plume of the Scheldt estuary were followed during and after a light-induced bloom by measuring changes in concentrations and stable isotope ratios in mesocosms after addition of C-bicarbonate showed a strong coupling between algal primary production and bacterial secondary production, while addition of 13 C-glucose revealed bacteria as a carbon source for eukaryotes. Tracing the 13 C into mesozooplankton, we identified selective grazin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 50 publications
0
22
1
1
Order By: Relevance
“…The low BGE, however, means that most of this up taken DOM is released as inorganic nutrients and CO 2 to the water column. The high bacterial production, similar to other tropical and temperate estuarine systems, suggests that this compartment also plays an important role as biomass sources for the next trophic levels LEE, 2011;TROUSSELLIER et al, 2005; VAN DEN MEERSCHE et al, 2011), but its major role in this system is as DOM remineralizer. The large allochthonous nutrient inputs along with the rapid DOM remineralization, supports the high primary productivity and biomass of the system (GUENTHER et al, 2015), which is the main source for the plankton consumers.…”
Section: Discussionmentioning
confidence: 99%
“…The low BGE, however, means that most of this up taken DOM is released as inorganic nutrients and CO 2 to the water column. The high bacterial production, similar to other tropical and temperate estuarine systems, suggests that this compartment also plays an important role as biomass sources for the next trophic levels LEE, 2011;TROUSSELLIER et al, 2005; VAN DEN MEERSCHE et al, 2011), but its major role in this system is as DOM remineralizer. The large allochthonous nutrient inputs along with the rapid DOM remineralization, supports the high primary productivity and biomass of the system (GUENTHER et al, 2015), which is the main source for the plankton consumers.…”
Section: Discussionmentioning
confidence: 99%
“…13 C labelling combined with modelling has been used successfully in previous mesocosm studies, allowing quantifying carbon flows and interactions in plankton food webs (Van den Meersche et al, 2004, 2011de Kluijver et al, 2010). However, there are some assumptions and potential errors that need attention.…”
Section: Methodological Considerations and Assumptionsmentioning
confidence: 99%
“…Engel et al, 2004b). Previous mesocosm studies focussed on nutrient replete situations and it was suggested that CO 2 effects on extracellular release would be more pronounced under nutrient limitation (Thingstad et al, 2008;de Kluijver et al, 2010). The results here show that bacterial production on phytoplankton exudation is also not enhanced with CO 2 in a post bloom situation.…”
Section: Co 2 Effectsmentioning
confidence: 99%
See 2 more Smart Citations